2019
DOI: 10.30534/ijatcse/2019/48842019
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Biometric Authentication Using Deep Learning Classifier for Securing of Healthcare Data

Abstract: Ensuring the security of healthcare data is becoming an increasingly important problem as modern technology is integrated into existing medical services. As a consequence of the adoption of healthcare data in the health care sector, it is becoming more and more common for a health professional to edit and view a patient's record using a tablet PC. To protect the patient's privacy, a secure authentication system to access patient records must be used. Yet, most Health apps used by consumers do not fall under fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…There were 17 studies about textual password authentication [17], [21], [23], [25 -27], [30], [32 -38], [41 -43] and three studies about graphical password authentication [22], [34], [39]. Seventeen studies discussed multifactor authentication [17], [19], [21], [23 -28], [30], [32 -37], [42] (as shown in Figure .2.). The review found that most scholars had chosen to focus on biometric authentication.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…There were 17 studies about textual password authentication [17], [21], [23], [25 -27], [30], [32 -38], [41 -43] and three studies about graphical password authentication [22], [34], [39]. Seventeen studies discussed multifactor authentication [17], [19], [21], [23 -28], [30], [32 -37], [42] (as shown in Figure .2.). The review found that most scholars had chosen to focus on biometric authentication.…”
Section: Resultsmentioning
confidence: 99%
“…There were some studies excluded from this review [48 -52] as they did not focus on types of authentication methods as a safety practice for information security. Of the 28 articles reviewed, 13 were based in India [20 -26], [30], [34 -37], [42]; four were from China [32], [33], [38], [44]; two from Saudi Arabia [18], [19] one from Poland [27]; one from the Czech Republic [31]; one from the United Arab Emirates [28]; one from Turkey [43]; one from Ukraine [40]; 1 from Jordan [17]; and one each from Zambia [29]; Philippines [39]; and the United States [41] (as shown in Figure 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The performance of the biometric verification system is estimated by measuring Genuine Acceptance Rate (GAR), False Acceptance Rate (FAR), and False Rejection Rate (FRR) [19]. Formula to calculate the FAR and FRR is given below: FAR= α / β × 100 Where, α = Number of accepted imposter β = Total number of imposter access FRR= γ / μ × 100 Where, γ = Number of rejected clients μ = Total number of client access GAR is defined as a percentage of legitimate users accepted by the biometric system and formula to calculate GAR is as follows:…”
Section: Performance Metrics Of Biometric Systemsmentioning
confidence: 99%
“…Colour Petri nets and timed colour Petri nets were introduced for password generation [11]. Password and authentication issues are addressed by various researchers in finding better solution towards rectification [18][19][20][21]. Motivated by these concepts we have defined a notion of diamond arrays generated by Petri nets.…”
Section: Introductionmentioning
confidence: 99%